The Influence of Work Life Balance and Job Crafting on Employee Performance at PT. XYZ - Lukiyana; Sintha Miranda (ORGANIZE: Journal of Economics, Management and Finance, 2024)
Through the use of quantitative research methodology and data collection techniques including observation, interviews and recording, this research seeks to determine and assess the influence of work-life balance and job crafting on employee performance at PT.XYZ. Head of the HRD Department of PT XYZ and karyawan acted as informants for data collection. Employees must always bear the costs, demands and obligations of their work. Employees will experience greater stress at work the more pressure there is in the workplace. An employee's capacity to handle work-related stress without disrupting their personal life is a key component of work-life balance. Employee adjustments to achieve a balance between job-related responsibilities and resources and their needs and skills are reflected in job creation. Job crafting has an impact on employee performance because when workers organize their tasks efficiently, improvements occur, increasing job satisfaction and productivity.